The meaning and effect of HIV/AIDS stigma for people living with AIDS and nurses involved in their care in the North West Province, South Africa - M. Greeff; R. Phetlhu (AOSIS, 2007)
The five countries with the highest HIV prevalence rates in the world are situated in southern Africa, and South Africa, with an estimated 4,7 million people living with HIV (PLWA), has more cases of HIV/AIDS than any other country. AIDS stigma and discrimination continue to impact on those living with and affected by the HIV disease and their health-care providers, particularly in southern Africa, where the burden of AIDS is so significant. Stigma has become a major problem in the provision o f care for PLWA in Africa. A five-year multinational African study on perceived AIDS stigma was undertaken. The North West Province in South Africa formed part of this study. The first phase focused on exploring and describing the meaning and effect o f stigma for PLWA and nurses involved in their care. This article focuses on the data for the North West Province, South Africa. An exploratory descriptive qualitative research design was used. Through focus groups the critical incident method was applied to gain respondents' emic and etic views. The study was conducted in the Potchefstroom district and the Kayakulu area. Purposive voluntary sampling was utilised. The open coding technique was used for data analysis. Three types of stigma (received, internal and associated stigma) and several dimensions for each type o f stigma were identified. Recommendations for interventions, a measuring scale and the formulation of a conceptual model were formulated.